Pelatihan Penerapan Gizi Seimbang Pada Masa Pandemi Covid-19 - Atika Nur Azizah (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2021)
The covid-19 pandemic (corona virus disease 2019) causes a decrease in the body's immune system. One of the things that can increase a toddler's immune system is eating a balanced nutritious diet. The purpose of the training on the application of balanced nutrition is to increase knowledge and skills about balanced nutrition. Balanced nutrition is necessary to promote a good immune system. The implementation method is in the form of training with lecture methods, discussions, and the practice of applying balanced nutrition to the management of the Nasyiatul Aisyiyah Rawalo Branch Manager. The result is an increase in knowledge by 60% and an increase in skills in the application of balanced nutrition by 85%.